Determinan Diabetes Mellitus pada Usia Remaja: Literatur Review - Sukurni, Sukurni (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Diabetes Mellitus (DM) is a chronic metabolic disease with a significantly increasing prevalence among young people. This phenomenon has become a global health challenge due to its long-term complications and its impact on individual productivity and quality of life. This study aims to identify the main determinants of DM in young people through a systematic literature review. The study uses the PCC framework (Population, Concept, Context) to define the focus of the review. Relevant literature was identified from databases such as PubMed, Scopus, and Google Scholar using a combination of keywords like “Diabetes Mellitus,” “young adults,” and “risk factors.” Inclusion criteria included studies published in the last 10 years, written in English or Indonesian, and discussing DM risk factors in individuals aged ≤40 years. The data obtained were analyzed narratively and systematically. Based on the analysis, the determinants of DM in young people involve genetic, environmental, and behavioral factors. Genetic factors, such as FTO gene variants, significantly increase the risk of DM. Environmental factors, including air pollution exposure and low socioeconomic status, also play a crucial role. Moreover, unhealthy lifestyles, such as physical inactivity, high-sugar diets, and sleep disturbances, are major contributors. Research indicates that behavioral factors are the most modifiable determinants for preventing DM in young people. DM in young people is a multifactorial condition that requires a multidimensional preventive approach.